A Bibliometric Analysis of Content Marketing and Consumer Behavior in the Digital Age - Loso Judijanto (Sciences du Nord Economics and Business, 2025)
This study presents a comprehensive bibliometric analysis of academic literature at the intersection of content marketing and consumer behavior in the digital age. Using data retrieved from the Scopus database and analyzed through VOSviewer, the study explores the intellectual structure, thematic evolution, and global collaboration patterns shaping this interdisciplinary field. The analysis identified key contributors, influential publications, and dominant research clusters centered around marketing strategy, consumer engagement, digital platforms, and behavioral psychology. Temporal visualization revealed a thematic shift from traditional advertising and decision-making models toward recent emphases on artificial intelligence, sustainability, and social media marketing. The United States emerged as the most prolific and collaborative contributor, with increasing participation from countries in Asia and the Middle East. The findings offer valuable insights for scholars and practitioners seeking to navigate and contribute to the evolving discourse on digital consumer behavior and content-driven marketing strategies. This study also highlights future research directions, including ethical personalization, AI-driven engagement, and culturally adaptive marketing practices.